2010
DOI: 10.1128/iai.00882-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of RpoS in Virulence of Pathogens

Abstract: Understanding mechanisms of bacterial pathogenesis is critical for infectious disease control and treatment.Infection is a sophisticated process that requires the participation of global regulators to coordinate expression of not only genes coding for virulence factors but also those involved in other physiological processes, such as stress response and metabolic flux, to adapt to host environments. RpoS is a key response regulator to stress conditions in Escherichia coli and many other proteobacteria. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(159 citation statements)
references
References 157 publications
(195 reference statements)
5
153
0
1
Order By: Relevance
“…s S activity and the rdar morphotype (red, dry and rough) (White & Surette, 2006;Dong & Schellhorn, 2010). Primarily, the authors observed a significantly lower prevalence of these two phenotypes in B2 than in B1 strains.…”
Section: Discussionmentioning
confidence: 73%
“…s S activity and the rdar morphotype (red, dry and rough) (White & Surette, 2006;Dong & Schellhorn, 2010). Primarily, the authors observed a significantly lower prevalence of these two phenotypes in B2 than in B1 strains.…”
Section: Discussionmentioning
confidence: 73%
“…RpoS has been shown to regulate virulence factors in E. coli, S. typhimurium and several other species involved in both animal and plant pathogenesis (Dong & Schellhorn, 2010). The pathogenesis of the S39006 rpoS mutant was investigated using potato and C. elegans as model hosts.…”
Section: The Srnas Dsra and Rpra Regulate Pig Productionmentioning
confidence: 99%
“…Role of rpoS in stress tolerance E. coli RpoS has been shown to play a critical role in coordinating the expression of genes involved in withstanding various stresses, including oxidative stress and starvation (Dong & Schellhorn, 2010). Therefore, the rpoS mutant was investigated for its ability to withstand different stresses.…”
Section: Rpos Is a Repressor Of Swimming And Swarming Motilitymentioning
confidence: 99%
“…RpoS, Salmonella türlerinin en önemli virülans faktörlerinden olup, besin yokluğu veya kısıtlaması ile pH ve sıcaklık değişimleri gibi stres faktörlerine maruz kaldığı zaman, bakterinin bu olumsuz koşullara dayanmasını ve canlı kalmasını sağlamaktadır 28 . Bu amaçla bakteri, durağan ve çoğalma fazında pek çok gen eksprese eder.…”
Section: Alternatif Sigma Faktör σ S (Rpos) Regülatörüunclassified